Strategies for Mobile Web Design - Cazañas, Alex; Parra, Esther (Enfoque UTE, 2017)
This paper presents a literature review on the topic of web design, specifically with regard to mobile web design. The aim of the review is to identify and analyze major strategies and approaches to design for small-screen-size devices. Three strategies consistently appeared across the reviewed literature, namely, responsive web design, adaptive web design, and separate site. The analysis of these strategies intends to provide a clear understanding of their advantages and disadvantages, in terms of cost and user experience.